Acute Elevated Resistin Exacerbates Mitochondrial Damage and Aggravates Liver Steatosis Through AMPK/PGC-1α Signaling Pathway in Male NAFLD Mice - Wen, Fengyun; Shi, Zhuoyan; Liu, Xiaoping; Tan, Yuguang; Wei, Lan; Zhu, Xuemin; Zhang, Hui; Zhu, Xiaohuan; Meng, Xiangmiao; Ji, Weixia; Yang, Mengting; Lu, Zhaoxuan (Hormone and Metabolic Research, 2020)
Resistin was identified as a link between obesity and insulin resistance and is associated with many diseases in mice. Deciphering the related development and molecular mechanism is necessary for the treatment of these diseases. Previous studies have revealed that increased resistin levels are correlated with lipid accumulation and play a role in non-alcoholic fatty liver disease (NAFLD) development. However, the exact mechanisms underlying these processes remain unclear. To further clarify whether acute elevated resistin level exacerbated liver steatosis, a high-fat diet-induced NAFLD animal model was used and treated with or without resistin for 6 days. We discovered that resistin altered mitochondrial morphology, decreased mitochondrial content, and increased lipid accumulation in HFD mice. qRT-PCR and western blot analysis showed that acute elevated resistin significantly altered the gene expression of mitochondrial biogenesis and liver lipid metabolism molecules in HFD mice. Consequently, in vitro experiments verified that resistin reduced the mitochondrial content, impaired the mitochondrial function and increased the lipid accumulation of palmitate-treated HepG2 cells. Additionally, we demonstrated that resistin upregulated proinflammatory factors, which confirmed that resistin promoted the development of inflammation in NAFLD mice and palmitate-treated HepG2 cells. Signaling-transduction analysis demonstrated that acute elevated resistin aggravated liver steatosis through AMPK/PGC-1α pathway in male mice. This reveals a novel pathway through which lipogenesis is induced by resistin and suggests that maintaining mitochondrial homeostasis may be key to treatments for preventing resistin-induced NAFLD aggravation.
Keywords: insulin resistance; diabetes; adipokines; obesity; metabolic syndrome; lipid metabolism